Drought and civil war in Sub-Saharan Africa - Mathieu Couttenier; Raphaël Soubeyran (Fondazione Eni Enrico Mattei (FEEM), 2010)
In this paper, we show that drought has a positive effect on the incidence of civil war over the 1945-2005 period in Sub-Saharan Africa. We use the Palmer Drought Severity Index which is a richer measurement of drought than the measures used in the literature (rainfall and temperature) as it measures the accumulation of water in the soil in taking into account the temperature and the geological characteristics of the soil. We show that the risk of civil war increases by more than 42% from a 'normal' climate to an 'extremely drought' climate. Surprisingly, only 2.5% of this effect is channeled through economic growth.
Keywords: O10; O55; P0; Q0; 330; Climate Change; Drought; Civil War